2022
DOI: 10.1063/5.0094402
|View full text |Cite
|
Sign up to set email alerts
|

The role of viscosity ratio in Janus drop impact on macro-ridge structure

Abstract: An interaction of liquid and solid surfaces upon impact has made great progress in understanding the principle behind impinging compound drops, such as single-interface Janus and core–shell configurations, for controlling drop mobility on the surfaces. Despite advancement of recent technologies, fundamentals of how viscosity ratios of Janus drops affect post-impact dynamics on anisotropic surfaces are still unknown. Here, we numerically investigate the asymmetric impact dynamics of Janus drops on a non-wettabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…Approximately 80% of the W-part or more (Ω ≥ 0.8) can be separated from the G-part at the We w thresholds. It is found that the We w threshold for separation at D 0 = 3.0 mm is almost similar to that observed at D 0 = 2.0 mm (We c,w ~40) [28]. It is found that Ω decreases slightly with increasing We w and α, which can be seen by the triangle symbol's size described in Figure 4e.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…Approximately 80% of the W-part or more (Ω ≥ 0.8) can be separated from the G-part at the We w thresholds. It is found that the We w threshold for separation at D 0 = 3.0 mm is almost similar to that observed at D 0 = 2.0 mm (We c,w ~40) [28]. It is found that Ω decreases slightly with increasing We w and α, which can be seen by the triangle symbol's size described in Figure 4e.…”
Section: Resultssupporting
confidence: 72%
“…In other words, the higher the viscosity ratio, the easier it is for the W-part to separate from the G-part. It is found that the Wew threshold for separation at D0 = 1.33 mm is slightly higher than that observed at D0 = 2.0 mm (Wec,w ~ 40) [28]. In addition, the volume ratio of the separated W-part decreases slightly with increasing Wew and α, which can be seen by the triangle symbol's size described in Figure 3e.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations